Fuzzy logic control - Khalid, Marzuki (Penerbit UTM Press, 1993)
Although fuzzy logic theory was proposed about three decades ago, it is only until recently that fuzzy control technology has been successfully applied to many industrial systems and domestic appliances. Much of these developments is mainly due to a better understanding of the concept of fuzzy logic, its simplicity of implementation, and its feasibility in hardware development. This article intends to provide a simple but clear understanding on the concept of fuzzy logic and its application to control systems (therefore not intended for those who have already understood the basic principles of fuzzy logic control). A simulation example is given on the development and operation of a fuzzy logic controller for a multi-variable water bath temperature control system. C-pseudocodes are given in the Appendices to clarify the water bath fuzzy control algorithms.